1960
DOI: 10.1017/s0021859600021262
|View full text |Cite
|
Sign up to set email alerts
|

Studies on goat nutrition Part II. Digestible protein requirements for maintenance from balance studies

Abstract: With One Text-figure)In Part I of this series (Majumdar, 1960) the results of a study of the endogenous urinary nitrogen (EUN) and metabolic faecal nitrogen (MFN) excretions in goats were recorded. These determinations were undertaken with a view to assessing the minimum protein requirement for maintenance in that species. Using the EUN values as the basis of calculation the minimum protein requirement was determined to be 0-65 lb./lOOO lb. live weight (L.W.). Maynard (1951), while agreeing that the endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…(1978), working with adult castrated native Japanese goats, estimated a daily loss of 0-24 g N/kg W 1 ' 5 , while Akinsoyinu, Mba & Olubayo (1976) obtained for West African Dwarf goats the low value of 0-04 g/kg W 076 . Majumdar (1960a) found with Jamnapari goats that EUN losses were 0-052 g/kg live weight, which can be converted to 0-13 g/kg W 0 " 76 , close to the value obtained from the present experiment (0-12 g/kg W 075 ) for animals of a rather lower mean live weight, and similar to the accepted values for sheep and cattle. The value for West African Dwarf goats is surprisingly low and must be treated with some caution until corroborative evidence is available, as it suggests that these animals have an exceptionally efficient metabolism with a minimal loss of nitrogen from the degradation and replacement of protein structures and.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…(1978), working with adult castrated native Japanese goats, estimated a daily loss of 0-24 g N/kg W 1 ' 5 , while Akinsoyinu, Mba & Olubayo (1976) obtained for West African Dwarf goats the low value of 0-04 g/kg W 076 . Majumdar (1960a) found with Jamnapari goats that EUN losses were 0-052 g/kg live weight, which can be converted to 0-13 g/kg W 0 " 76 , close to the value obtained from the present experiment (0-12 g/kg W 075 ) for animals of a rather lower mean live weight, and similar to the accepted values for sheep and cattle. The value for West African Dwarf goats is surprisingly low and must be treated with some caution until corroborative evidence is available, as it suggests that these animals have an exceptionally efficient metabolism with a minimal loss of nitrogen from the degradation and replacement of protein structures and.…”
Section: Discussionsupporting
confidence: 90%
“…The present experiment has estimated maintenance levels to be 0-314 g digestible N/kg W 07S , or 0-688 g dietary N/kg W 0 7 6 both by extrapolation methods, and 0-682 g dietary N/kgW°-76 by a factorial method, close to the values obtained by Itoh et al (1978), and Majumdar (1960a and b).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present trials the digestible nitrogen required for nitrogen equilibrium by 21 kg Barbados Blackbally sheep was calculated from nitrogen balance, factorially and from feeding trial data and found to vary from 4-26 to 6-94 g/day depending on the method of estimation. These values are much higher than those referred to above but agree more closely with those reported by Majundar (1960) for goats. It is difficult to explain the above differences.…”
Section: Protein Requirement For Maintenancesupporting
confidence: 92%